2001
DOI: 10.1897/1551-5028(2001)020<1325:ioaiar>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Androstenedione in a River Containing Paper Mill Effluent

Abstract: Effluent from a paper mill discharging into the Fenholloway River, Taylor County, Florida, USA, contains chemicals that masculinize females of the resident population of eastern mosquitofish (Gambusia holbrooki), as evidenced in females by elongated anal fins, which is normally a male-specific trait. To identify androgenic components in the effluent, water collected from the Fenholloway River and a control tributary was fractionated using solid-phase extraction and reverse-phase high-performance-liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
80
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 32 publications
6
80
1
3
Order By: Relevance
“…It has been hypothesized that bacterial biotransformation of plant sterols in the effluent generates the androgens responsible for the observed masculinization of female mosquitofish exposed to paper mill effluent (49). Recently, it was reported that androstenedione was present after a chemical characterization of the effluent from a paper mill plant in Florida (50). Using a number of in vitro receptor binding and gene expression assays, our laboratory in collaboration with others has not found sufficient androstenedione concentration in Fenholloway River water samples to support the reported significant androgenic actions of this effluent, however (15).…”
mentioning
confidence: 91%
“…It has been hypothesized that bacterial biotransformation of plant sterols in the effluent generates the androgens responsible for the observed masculinization of female mosquitofish exposed to paper mill effluent (49). Recently, it was reported that androstenedione was present after a chemical characterization of the effluent from a paper mill plant in Florida (50). Using a number of in vitro receptor binding and gene expression assays, our laboratory in collaboration with others has not found sufficient androstenedione concentration in Fenholloway River water samples to support the reported significant androgenic actions of this effluent, however (15).…”
mentioning
confidence: 91%
“…Special attention has been directed toward plant sterols metabolites as androstenedione for being an active hormonally compound capable of inducing androgenic effects in organisms (Malaviya and Gomes 2008;Lambert and Edwards 2017). This compound has been found in kraft mill effluents, even after being treated by activated sludge (Chamorro et al 2016a) at a concentration of 2.4 nM sediment near to discharge and 0.14 nM in the water column (Jenkins et al 2001(Jenkins et al , 2003; Van den Heuvel et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phytosterols in pulp and paper mill effluents were transformed to androgens by microorganisms in river sediments, consequently influencing fish development (Jenkins et al, 2001(Jenkins et al, , 2003. Steroid hormones have been frequently detected in various environmental matrices, including soil, groundwater, surface water and sediments (Ying et al, 2002).…”
Section: Introductionmentioning
confidence: 99%